2022
DOI: 10.3389/fcvm.2022.990182
|View full text |Cite
|
Sign up to set email alerts
|

Optimal dose of tirzepatide for type 2 diabetes mellitus: A meta-analysis and trial sequential analysis

Abstract: ObjectiveThe purpose of this study is to evaluate the optimal dose of tirzepatide (TZP) for the treatment of type 2 diabetes mellitus (T2DM) by meta-analysis and trial sequential analysis (TSA).MethodsClinical trials of TZP for T2DM were obtained by searching 8 databases with a time limit from database creation to May 2022. Mean differences (MD) and 95% confidence intervals (95%CI) were used for continuous variables, and relative risk (RR) and 95%CI were used for dichotomous variables.ResultsCompared with TZP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 55 publications
1
6
2
Order By: Relevance
“…Previous studies (25-27) showed that reducing refined sugar and fat intake may help to reduce GADE by GLP-1 RAs, but whether these methods are suitable for TZP needs to be confirmed by further research. The current view is that, consistent with GLP-1 RAs, the higher dose of TZP is associated with more GADE (22). But our result did not seem to support this point.…”
Section: Discussioncontrasting
confidence: 93%
“…Previous studies (25-27) showed that reducing refined sugar and fat intake may help to reduce GADE by GLP-1 RAs, but whether these methods are suitable for TZP needs to be confirmed by further research. The current view is that, consistent with GLP-1 RAs, the higher dose of TZP is associated with more GADE (22). But our result did not seem to support this point.…”
Section: Discussioncontrasting
confidence: 93%
“…In particular, the rate of drug discontinuation due to AEs was up to 10% (8%-13%) with the 15-mg dose of tirzepatide. The study by Yu and our colleagues [ 27 ] and our study have similar findings for no significant difference in AEs including MACE, hypertension, cancer, and hypoglycemic events with 3 different doses of tirzapatide. In a study by Karagiannis et al [ 28 ], the authors found 2-fold higher odds of study drug discontinuation at the highest dose of tirzepatide.…”
Section: Discussionsupporting
confidence: 87%
“…For the majority of GI AEs, we found a significant dose-dependent relationship with higher dose being associated with higher incidence rates of AEs. A recent study by Yu et al [ 27 ] reported increased total AEs and GI AEs (relative risk [RR] 1.17; P = .02) with 10 mg, and increased total AEs (RR 1.10; P = .0001) with 15-mg compared to the 5-mg dose of tirzepatide. No statistically significant differences were observed in total AEs and GI AEs for 15-mg compared to 10-mg tirzepatide.…”
Section: Discussionmentioning
confidence: 99%
“…A recent trial sequential analysis exploring the optimal dose of tirzepatide in patients with DM, showed a dose dependent effect on glycemic control and weight reduction, without a significant increase in the rate of adverse events with higher doses. 131 Interestingly, pooled data from SURMOUNT-1 and SURPASS clinical trials programs showed a significant relative risk reduction in major adverse CV events and CV death, by 48 and 49% respectively, with Tirzepatide, compared to control. 132 …”
Section: Resultsmentioning
confidence: 99%